2005
DOI: 10.1152/ajpendo.00155.2005
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase kinase activity and phosphorylation of AMP-activated protein kinase in contracting muscle of sedentary and endurance-trained rats

Abstract: This study was designed to examine activity of AMP-activated protein kinase kinase (AMPKK) in muscles from nontrained and endurance-trained rats. Rats were trained 5 days/wk, 2 h/day for 8 wk at a final intensity of 32 m/min up a 15% grade with 30-s sprints at 53 m/min every 10 min. Gastrocnemius muscles were stimulated in situ in trained and nontrained rats for 5 min at frequencies of 0.4/s and 1/s. Gastrocnemius LKB1 protein, a putative component of the AMPKK complex (LKB1, STRAD, and MO25), increased approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…Activation of AMPK in skeletal muscle has been shown in a variety of systems including in vitro / in vivo contraction, pharmacological activators and transgenic animals (Nielsen et al 2003b;Sakamoto et al 2004b;Atherton et al 2005;Jorgensen et al 2005;Toyoda et al 2006). Current evidence suggests that isoform specific AMPK activation occurs in a time, intensity, fibre-type and mode-specific manner and exercise-induced contraction of skeletal muscle in vivo has been clearly shown to up-regulate AMPK activity (Durante et al 2002;Nielsen et al 2003b;Yu et al 2003;Frøsig et al 2004;Atherton et al 2005;Hurst et al 2005;McConell et al 2005;Sriwijitkamol et al 2005;Taylor et al 2005;Wojtaszewski et al 2005;Toyoda et al 2006).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of AMPK in skeletal muscle has been shown in a variety of systems including in vitro / in vivo contraction, pharmacological activators and transgenic animals (Nielsen et al 2003b;Sakamoto et al 2004b;Atherton et al 2005;Jorgensen et al 2005;Toyoda et al 2006). Current evidence suggests that isoform specific AMPK activation occurs in a time, intensity, fibre-type and mode-specific manner and exercise-induced contraction of skeletal muscle in vivo has been clearly shown to up-regulate AMPK activity (Durante et al 2002;Nielsen et al 2003b;Yu et al 2003;Frøsig et al 2004;Atherton et al 2005;Hurst et al 2005;McConell et al 2005;Sriwijitkamol et al 2005;Taylor et al 2005;Wojtaszewski et al 2005;Toyoda et al 2006).…”
Section: +mentioning
confidence: 99%
“…Indeed, endurance exercise-induced activation of AMPK is predictable given its ability to increase ATP regeneration via fat oxidation to meet the demands of prolonged lowintensity contraction. Interestingly, this exercise response seems to be dependent on the adaptive state of the muscle as evidence exists to demonstrate that short-term and chronic aerobic training reduces the acute AMPK response to prolonged and intermittent sub-maximal exercise (Durante et al 2002;Yu et al 2003;Hurst et al 2005;McConell et al 2005). …”
Section: +mentioning
confidence: 99%
“…Two studies [63,64] have shown that exercise training increases LKB1 protein content, concomitant with elevated expression of the transcriptional coactivator PGC1 in rat skeletal muscle [64]. This occurs despite reportedly decreased AMPK kinase activity [63,65]. In studies of muscle-specific LKB1 knockout mice [37,66 •• ], it was shown that LKB1 is a critical regulator of exercise capacity and basal mitochondrial function.…”
Section: Role Of Lkb1 and Ampk In Metabolic Adaptationmentioning
confidence: 99%
“…The work identifying this AMPKK was done on liver and cells in culture, and not skeletal muscle. LKB1, MO25 protein, and STRAD mRNA were subsequently shown to be expressed in skeletal muscle (13,24). Three groups reported marked reductions in resting and contracting muscle AMPK activity and phosphorylated AMPK in muscle-specific LKB1 knockout (MLKB1KO) mice, implying that LKB1 is a component of the AMPKK of skeletal muscle (9,21,34).…”
mentioning
confidence: 99%